Progesterone inhibition of oxytocin signaling in endometrium - Bishop, Cecily V. (Frontiers in Neuroscience, 2013)
Expression of the oxytocin receptor (OXTR) in the endometrium of ruminant species is regulated by the ovarian steroids progesterone (P) and estradiol (E). Near the end of the estrous cycle, long-term exposure of endometrial epithelial cells to P results in loss of genomic P receptors (PGRs), leading to an increase in E receptors (ERs). Genomic regulation of the OXTR is mediated via suppression of ER signaling by P. Upon OT binding at the plasma membrane of endometrial cells, a signaling cascade is generated stimulating release of prostaglandin F2alpha (PGF2alpha). Transport of PGF2alpha to the ovary results in release of OT by luteal cells in a positive feedback loop leading to luteal regression. This signaling cascade can be rapidly blocked by exposing endometrial cells to physiologic levels of P. This mini review will focus on the mechanisms by which P may act to block OXTR signaling and the luteolytic cascade in the ruminant endometrium, with special focus on both non-genomic signaling pathways and non-receptor actions of P at the level of the plasma membrane. While this review focuses on ruminant species, non-classical blockage of OXTR signaling may be important for fertility in women.